The eyes are silent ... the heart desires to speak: exploring masculinities in South Asia - Roy, Rahul (2001)
Rahul Roy explores the culture of masculinity and violence against women (VAW) in South Asia, arguing that film making can be an effective tool encouraging young men to reflect on their relationships with women and challenge the dominant paradigms of `male behaviour'. - Reproduced
Keywords: Violence - South Asia; Women - Crimes against; Women - South Asia; Women